2018
DOI: 10.24293/ijcpml.v14i2.902
|View full text |Cite
|
Sign up to set email alerts
|

Prediksi Jumlah Sel Limfosit T Cd4+ Menggunakan Nilai TLC (Total Lymphocyte Count) Pada Penderita Hiv/Aids

Abstract: AIDS is a severe disease caused by Human Immunodeficiency Virus (HIV) that affects patient’s immune system, especially CD4+ Tcells (CD4). Hence, CD4 count is used as parameter to starting ARV treatment or monitoring the progress of the disease. However, themeasurement of CD4 is expensive and available in big hospitals. In small or remote hospitals there are no means to measure the CD4.Some studies suggest that in an area where CD4 count is unavailable, the total lymphocyte count (TLC) of HIV/AIDS patients can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…CD4 cells are the largest part of T lymphocytes, which is 34-67%. 3,19,20 In HIV infection, selective reduction in CD4 cells is found due to the direct effects of the virus or the body's immune response. This selective reduction is due to the tropism of the virus to infect CD4 cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CD4 cells are the largest part of T lymphocytes, which is 34-67%. 3,19,20 In HIV infection, selective reduction in CD4 cells is found due to the direct effects of the virus or the body's immune response. This selective reduction is due to the tropism of the virus to infect CD4 cells.…”
Section: Resultsmentioning
confidence: 99%
“…1,2 The highest number of cases of infection were DKI Jakarta with 51,981 people, followed by East Java with 39,633 people, Papua 29,083 people, West Java 28,964 people and Central Java with 22,292 people. 2,3 Based on data from the Directorate General of Disease Prevention and Control, the Ministry of Health of the Republic of Indonesia in 2017 in East Nusa Tenggara Province the Human Immunodeficiency Virus (HIV) is a retrovirus originating from the retroviridae family of the genus lentivirus that infects and damages cells that have a molecule Cluster of Differentiation 4 (CD4), especially T lymphocytes that have receptors with high affinity for HIV. Total lymphocyte count / TLC has been proposed as an alternative guide to CD4 in limited health facilities.…”
Section: Introductionmentioning
confidence: 99%
“…14 In a study by Rostina (2008), TLC was calculated from leukocyte x lymphocytes in percentage based on the Ministry of Health of the Republic of Indonesia. 15…”
Section: Vd Serum Leucocyte and Lymphocyte Evaluationmentioning
confidence: 99%
“…11 Several other studies have discussed the use of TLC as a surrogate for HIV progression over the past years. [13][14][15] Other studies have suggested that TLC combined with blood hemoglobin level provides more sensitive predictions for the progression of HIV. [16][17][18] Other data highlight further hematological dysfunctions in HIV patients, such as normocytic normochromic anemia, thrombocytopenia, and monocytosis, which are associated with immunological and clinical severity and stage of the disease and tend to improve after ART initiation.…”
Section: Introductionmentioning
confidence: 99%